Association Between Gender Confirmation Treatments and Perceived Gender Congruence, Body Image Satisfaction, and Mental Health in a Cohort of Transgender Individuals. Issue 4 (17th February 2018) - Owen-Smith, Ashli A.; Gerth, Joseph; Sineath, R. Craig; Barzilay, Joshua; Becerra-Culqui, Tracy A.; Getahun, Darios; Giammattei, Shawn; Hunkeler, Enid; Lash, Timothy L.; Millman, Andrea; Nash, Rebecca; Quinn, Virginia P.; et al.
Abstract: Background: Transgender individuals sometimes seek gender confirmation treatments (GCT), including hormone therapy (HT) and/or surgical change of the chest and genitalia ("top" and "bottom" gender confirmation surgeries). These treatments may ameliorate distress resulting from the incongruence between one's physical appearance and gender identity. Aim: The aim was to examine the degree to which individuals' body-gender congruence, body image satisfaction, depression, and anxiety differed by GCT groups in cohorts of transmasculine (TM) and transfeminine (TF) individuals. Methods: The Study of Transition, Outcomes, and Gender is a cohort study of transgender individuals recruited from 3 health plans located in Georgia, Northern California, and Southern California; cohort members were recruited to complete a survey between 2015–2017. Participants were asked about: history of GCT; body-gender congruence; body image satisfaction; depression; and anxiety. Participants were categorized as having received: (1) no GCT to date; (2) HT only; (3) top surgery; (4) partial bottom surgery; and (5) definitive bottom surgery. Outcomes: Outcomes of interest included body-gender congruence, body image satisfaction, depression, and anxiety. Results: Of the 2, 136 individuals invited to participate, 697 subjects (33%) completed the survey, including 347 TM and 350 TF individuals. The proportion of participants with low body-gender congruence scores was significantly higher in the "no treatment" group (prevalence ratio [PR] = 3.96, 95% CI 2.72–5.75) compared to the definitive bottom surgery group. The PR for depression comparing participants who reported no treatment relative to those who had definitive surgery was 1.94 (95% CI 1.42–2.66); the corresponding PR for anxiety was 4.33 (95% CI 1.83–10.54). Clinical Translation: Withholding or delaying GCT until depression or anxiety have been treated may not be the optimal treatment course given the benefits of reduced levels of distress after undergoing these interventions. Conclusions: Strengths include the well-defined sampling frame, which allowed correcting for non-response, a sample with approximately equal numbers of TF and TM participants, and the ability to combine data on HT and gender confirmation surgeries. Limitations include the cross-sectional design and the fact that participants may not be representative of the transgender population in the United States. Body-gender congruence and body image satisfaction were higher, and depression and anxiety were lower among individuals who had more extensive GCT compared to those who received less treatment or no treatment at all.